A reassessment of the Andean genus Myopella Malloch (Diptera: Anthomyiidae) - Michelsen, Verner (Zootaxa, 2023)
The small Andean genus Myopella Malloch with two included species, M. angustifrons Malloch and M. appendiculata (Stein), is re-examined with special attention to the morphology of the male and female abdomen and terminalia. Adult morphology corroborates the current position of Myopella as an Andean endemic genus of Anthomyiidae, but its position within the anthomyiid tree remains in doubt despite the newly attained morphological knowledge. The status of the name Myopinella Michelsen, as proposed recently to replace for the preoccupied name Myopella Malloch, is clarified.